A COMPARISON IN THERMAL-HYDRAULICS ANALYSIS OF PWR1000 USING FIXED AND TEMPERATURE FUNCTION OF THERMAL CONDUCTIVITY - Muhammad Darwis Isnaini; Etty Mutiara (Jurnal Pengembangan Energi Nuklir, 2016)
A COMPARISON IN THERMAL-HYDRAULICS ANALYSIS OF PWR-1000 USING FIXEDAND TEMPERATURE FUNCTION OF THERMAL CONDUCTIVITY. A study to analyze theinfluence of the fuel-cladding’s thermal conductivity on the sub-channel of pressurized waterreactor 1000 (PWR-1000) using COBRA-EN computer code was conducted. The purpose ofthis research is to gain complete understanding of sub-channel thermal-hydraulic aspectsrelated to fuel performance, especially the appropriate range of thermal conductivity of UO2fuel (kf) and zircaloy-4 cladding (kc) in order to obtain an accurate sub-channel analysisrelated to its safety behavior. The research was conducted by comparing the calculation withthe combination values of the fixed kf and kc, as well as the calculation using kf and kc astemperature function. The fixed kf using in this calculation were 5.26 W/m.K, 3.85 W/m.K,3.60 W/m.K, 3.18 W/m.K, 2.90 W/m.K, 2.53 W/m.K and 2.34 W/m.K, while the kc were13.0 W/m.K, 15.57 W/m.K, 16.75 W/m.K, 17.94 W/m.K and 18.69 W/m.K. The maximumfuel center linet emperature using kf and kca s temperature function (MATPRO) for hot sub -channel was 1717.65°C and taken as the reference in accepting the calculation result usingfixed thermal conductivity. The analysis was accepted, if the deviation between bothtemperature was in the range of -10% to 10%. This analysis results for hot sub-chan nelwas accepted for the calculation using value of kf in the range of 3.18 - 2.90 W/m.K for allall variation value of kcW. hile the calculation using value of koff 2.53 W/m.K was accepet dfor value of kc in the range of 16.76 - 18.69 W/m.K